2014
DOI: 10.1016/j.jval.2014.08.293
|View full text |Cite
|
Sign up to set email alerts
|

Global Economic Burden of Schizophrenia: A Systematic Review

Abstract: A767 49-89% of the total annual costs associated with schizophrenia. ConClusions: Schizophrenia imposes a substantial economic burden on society mainly driven by high indirect costs. The cost estimates varied due to methodology differences and costs included. The information of disease burden associated with schizophrenia is crucial to enable informed decision-making in allocating health care resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
168
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(182 citation statements)
references
References 0 publications
1
168
0
9
Order By: Relevance
“…In the US adult population, the 12-month prevalence of schizophrenia is 1.1% [1]. The educational and occupational performance of patients with schizophrenia is affected, resulting in one of the highest global disease burdens [2]. In 2002, the US societal economic burden of schizophrenia was reported to be US$62.7 billion [3], becoming US$155.7 billion in 2013 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the US adult population, the 12-month prevalence of schizophrenia is 1.1% [1]. The educational and occupational performance of patients with schizophrenia is affected, resulting in one of the highest global disease burdens [2]. In 2002, the US societal economic burden of schizophrenia was reported to be US$62.7 billion [3], becoming US$155.7 billion in 2013 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Second, many disabled people cannot go to work, so they may not earn money and may not be able to cover the costs of rehabilitation setting. So if policy makers find some arrangements help them to work, some parts of their financial concerns may be decreased (4). In this study we found the types of disabilities which had more effect on labor force participation.…”
Section: Discussionmentioning
confidence: 55%
“…Disabled people are such people who cannot work easily and need help (3). Ability of disabled population for working depends on the severity of disability and classification of it (4). In addition it depends on the type of work too.…”
Section: Introductionmentioning
confidence: 99%
“…Yaklaşık 15 yıllık çalışmadan geçen sürenin ülke ekonomisini de dolaylı olarak olumsuz etkilediği söylenebilir. Ulaşılan bu bulgu çalışmanın en çarpıcı sonucu olmakla birlikte, şizofreninin ekonomik yükünün ülke ve toplum için yüksek olduğunu gösteren çalışmaları destekler niteliktedir [17][18][19] . Hastalık sonrasında hiç çalışmayan hastaların %41 (n=41) oranında olduğu, %34'ünün hastalık sonrasında bir kez çalıştığı ve %13'ünün iki iş deneyiminin olduğu saptandı.…”
Section: Ortalama ± Ssunclassified